Multi-Layer IoT Security Framework for Ambient Intelligence Environments - Ion Bica; Bogdan-Cosmin Chifor; Ștefan-Ciprian Arseni; Ioana Matei (Sensors, 2019)
Ambient intelligence is a new paradigm in the Internet of Things (IoT) world that brings smartness to living environments to make them more sensitive; adaptive; and personalized to human needs. A critical area where ambient intelligence can be used is health and social care; where it can improve and sustain the quality of life without increasing financial costs. The adoption of this new paradigm for health and social care largely depends on the technology deployed (sensors and wireless networks), the software used for decision-making and the security, privacy and reliability of the information. IoT sensors and wearables collect sensitive data and must respond in a near real-time manner to input changes. An IoT security framework is meant to offer the versatility and modularization needed to sustain such applications. Our framework was designed to easily integrate with different health and social care applications, separating security tasks from functional ones and being designed with independent modules for each layer (Cloud, gateway and IoT device), that offer functionalities relative to that layer.